Flavors and essences from Joanović pharmacy - Dželajlija, Darko; Milošević Georgiev, Andrijana (Archives of Pharmacy, 2022)
Sima T. Joanović was born in Saravola and graduated in pharmacy in Budapest. From Timisoara, where he worked for a short time, he came to town of Debeljača and bought a pharmacy from Ambrosy Sándór, which was located in the building of the old municipality. He moved the pharmacy to a new residential and business building on the then Elisabeth Square. In addition to the highly developed semi-industrial production of galenic, cosmetic and perfumery preparations, food aromas and essences were also produced  in the pharmacy, which was not the case with other pharmacies. The essences were made in a galenic laboratory from 1910 to 1945. These food essences and flavors are sold wholesale and retail in consumer goods stores as well as cash on delivery. The pharmacy was especially known for the production of essences for various types of rum, brandy, liqueur and flavors for non-alcoholic beverages. Of the rum essences, the essences for Jamaica, Kingston and Demara rum were especially famous. Essences for making cold-processed were in great demand. Essences for making liqueurs were a sought-after item, the pharmacy produced a whole range of different essences. From the flavors for making non-alcoholic refreshing drinks the pharmacy produced lemon, orange, strawberry, raspberry, kabeza, pineapple, etc. The pharmacy printed instructions for making food products using these essences and flavors that were distributed to consumers. These instructions were thrown out of the plane as a special attraction at the famous large fairs that are still held in town of Debeljača.